2005 IEEE Congress on Evolutionary Computation
DOI: 10.1109/cec.2005.1555017
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating a Metropolis method in a Distribution Estimation using Markov Random Field Algorithm

Abstract: CopyrightItems in 'OpenAIR@RGU', The Robert Gordon University Open Access Institutional Repository, are protected by copyright and intellectual property law. If you believe that any material held in 'OpenAIR@RGU' infringes copyright, please contact openair-help@rgu.ac.uk with details. The item will be removed from the repository while the claim is investigated. Copyright © [2005] IEEE. Reprinted from Proceedings of the IEEE Congress on Evolutionary Computation (CEC 2005)This material is posted here with permis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Notice that, as with Is-DEUM m (shown in Figure (3)), Is-DEUM g only has a single generation. As shown in [26], we could easily incorporate a multiple generation scheme in Is-DEUM g . We found that, for the Ising spin …”
Section: B Deum With Gibbs Samplermentioning
confidence: 99%
See 1 more Smart Citation
“…Notice that, as with Is-DEUM m (shown in Figure (3)), Is-DEUM g only has a single generation. As shown in [26], we could easily incorporate a multiple generation scheme in Is-DEUM g . We found that, for the Ising spin …”
Section: B Deum With Gibbs Samplermentioning
confidence: 99%
“…This has also been illustrated in[26] for the Onemax problem, where a Zero-Temperature Metropolis algorithm was able to find the solution in single generation3 Though it is straightforward to form a child population once we know how to sample from the MRFs (see[26] for an example)…”
mentioning
confidence: 97%
“…The aim here is to provide an overview of some of the working example of DEUM. More complete description of these and other DEUM algorithms together with detail experimental results can be found in [9,10,[22][23][24][25].…”
Section: Instances Of Deummentioning
confidence: 99%
“…Within DEUM, direct sampling is used to generate new solutions with a high probability of being high in fitness [54,53,5]. This direct sampling of the fitness model rather than the fitness function has the benefit that the model can make the problem easier for the search part of the algorithm -the smoothing effect described in [63].…”
Section: Applicationsmentioning
confidence: 99%